Optical coherence tomography measurements and analysis methods in optical coherence tomography studies of diabetic macular edema - Browning, David J; Glassman, Adam R; Aiello, Lloyd P; Bressler, Neil M; Bressler, Susan B; Danis, Ronald P; Davis, Matthew D; Ferris, Frederick L; Huang, Suber S; Kaiser, Peter K; Kollman, Craig; Sadda, Srinavas; et al. (Ophthalmology (Rochester, Minn.), 2008)
To evaluate optical coherence tomography (OCT) measurements and methods of analysis of OCT data in studies of diabetic macular edema (DME). Associations of pairs of OCT variables and results of 3 analysis methods using data from 2 studies of DME. Two hundred sixty-three subjects from a study of modified Early Treatment of Diabetic Retinopathy Study (mETDRS) versus modified macular grid (MMG) photocoagulation for DME and 96 subjects from a study of diurnal variation of DME. Correlations were calculated for pairs of OCT variables at baseline and for changes in the variables over time. Distribution of OCT measurement changes, predictive factors for OCT measurement changes, and treatment group outcomes were compared when 3 measures of change in macular thickness were analyzed: absolute change in retinal thickness, relative change in retinal thickness, and relative change in retinal thickening. Concordance of results using different OCT variables and analysis methods. Center point thickness correlated highly with central subfield mean thickness (CSMT) at baseline (0.98-0.99). The distributions of changes in CSMT were approximately normally distributed for absolute change in retinal thickness and relative change in retinal thickness, but not for relative change in retinal thickening. Macular thinning in the mETDRS group was significantly greater than in the MMG group when absolute change in retinal thickness was used, but not when relative change in thickness and relative change in thickening were used. Relative change in macular thickening provides unstable data in eyes with mild degrees of baseline thickening, unlike the situation with absolute or relative change in retinal thickness. Central subfield mean thickness is the preferred OCT measurement for the central macula because of its higher reproducibility and correlation with other measurements of the central macula. Total macular volume may be preferred when the central macula is less important. Absolute change in retinal thickness is the preferred analysis method in studies involving eyes with mild macular thickening. Relative change in thickening may be preferable when retinal thickening is more severe.